Sale Price of Holstein Feeder Steer Lots Relative to Other Breed Descriptions Sold Through Superior Livestock Video Sales from 2010 Through 2018 - E. D. McCabe; M. J. Smith; M. E. King; K. E. Fike; G. M. Rogers; K. G. Odde (Kansas Agricultural Experiment Station Research Reports, 2020)
Objective:The objective of this study was to determine the relative value of Holstein feeder steer lots compared to steer lots of other breed descriptions sold through video auctions while adjusting for all other factors that significantly influenced sale price. Study Description:Data were analyzed from 14,075 lots of feeder steers sold via 211 livestock video auctions from 2010 through 2018. All lot characteristics that could be accurately quantified or categorized were used to develop a multiple regression model with backwards selection. A lot was categorized into one of four breed descriptions: 1) English, English crossed; 2) English-Continental crossed; 3) Brahman influenced; and 4) Holstein. The Bottom Line:The relative price discount for Holstein feeder steer lots compared with other breed descriptions appears to have increased from 2010–2018, and thus is likely indicating lessening interest in the feedlot sector to feed Holstein steers to harvest.
Keywords: feeder cattle; Holstein video auctions